(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Objectives : To determine the outcome of pneumothorax in term and post term neonates. Study Design : Neonates presented with respiratory distress and diagnosed pneumothorax by X-ray at the time of admission or during the course of hospital stay were included in this study. Results: Total 49 cases were included for the study, among them 29(59.18%)were male and 20(40.82%) female, 42(85%)babies cured and 7(15%)expired. Thirty-five (71.46%) delivered by LUCS, 14(28.57%) by NVD. Pneumothorax associated with maternal risk factors like UTI 10(21.2%), PROM 5(10.2%), GDM 2(4.2%)cases, PIH 1(2.0%), PET 1(2%), were observed. No maternal risk factor has been identified in 25(51%)cases and 4(8.1%)cases due to other reason. Nineteen neonates (38.77%) with meconium aspiration syndrome, 14(28.57%) required PPV, 10(20.40%) with pneumonia 2(4.08%) with congenital heart disease, 2(4.08%) with TTN, pneumothorax 2(4.02%). Total 40(81.63%) cases were in patient, only 3(7.5%) of them died, 9(18.36%) babies were out patient among them 4(8.16%) died, (P value Â0.001). Significant death were seen among those who admitted after 24 hours of age, 3 out of 6 cases). Four (8.16) out of 36(73.4%)expired who admitted before 24 hours of age, (P value Â 0.001.) Pneumothorax were managed by nitrogen wash out 29(59.18%), 5(10.20%) needle aspiration with high flow oxygen, 5(10.20%)needed needle aspiration, chest tube with high flow oxygen. Ten (20.40%)babies needed needling, chest tube drainage with ventilator, among them 6(12.24%)expired and 4 survived. No death were observed among the neonates who were managed with high flow oxygen. Conclusions: High index of suspicion, prompt diagnosis by cold light and urgent portable X-ray and immediate intervention is needed for life saving and better outcome J. Paediatr. Surg. Bangladesh 5(1): 3-7, 2014 (January)